Ecophysiology of the Southern Highbush blueberry cv. Biloxi in response to nitrogen fertigation - Nunes de Lima, Firmino; Yamanishi, Osvaldo Kiyoshi; Pires, Márcio de Carvalho; Saba, Elias Divino; Pereira, Aline Rodrigues; Miranda, Gabriel Soares (Comunicata Scientiae, 2020)
In Brazil, the nutritional requirements of the blueberry are not sufficiently known, thus requiring further research on the management of mineral fertilization. In this perspective, this work aimed to evaluate physiological attributes of Southern Highbush blueberry plants cv. Biloxi as a function of nitrogen fertigation in Brasília-DF. The experiment was conducted from August 2018 to July 2019, in the Fruit Sector of the Experimental Biology Station of the University of Brasilia (UnB), Federal District. This experiment adopted a randomized block design, with four treatments: 10; 20; 30, and 40 g of N plant-1, 8 replications, and 5 plants per experimental plot. The following variables were measured: net photosynthesis rate (A), transpiration (E), stomatal conductance (gs), internal CO2 concentration (Ci), instantaneous water-use efficiency (WUE), carboxylation efficiency (CE), SPAD index (SPAD) and leaf nitrogen (N). There was an effect of the different nitrogen doses applied on the physiological attributes. The plants of the blueberry cultivar Biloxi increased their photosynthetic rates at doses up to 30 g of N plant-1. Nitrogen rates did not influence stomatal conductance nor did they provide improvements in the carboxylation efficiency of the blueberry plants. Under the conditions of the present work, the highest N leaf contents were obtained with the application of 30 g N plant-1, and values above this concentration did not correspond to higher net photosynthesis rates, transpiration, and CO2 concentration in the leaf mesophyll.